2021
DOI: 10.3389/fmolb.2021.683671
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Metabolism of Leaf Nodules in Ardisia crenata and Psychotria punctata

Abstract: Root-microbe interaction and its specialized root nodule structures and functions are well studied. In contrast, leaf nodules harboring microbial endophytes in special glandular leaf structures have only recently gained increased interest as plant-microbe phyllosphere interactions. Here, we applied a comprehensive metabolomics platform in combination with natural product isolation and characterization to dissect leaf and leaf nodule metabolism and functions in Ardisia crenata (Primulaceae) and Psychotria punct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 89 publications
(146 reference statements)
0
11
0
Order By: Relevance
“…These bacteria are able to become internalized at meristems when leaf cells are forming. It has also been shown that some bacteria may be absorbed from soils and transported to leaves [ 85 ]. We observed that these trichome openings also serve as exit points for endophytes to colonize the leaf surface, providing a mechanism that helps to explain the provenance of some phyllosphere microbes, including many seed-derived proteobacteria [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These bacteria are able to become internalized at meristems when leaf cells are forming. It has also been shown that some bacteria may be absorbed from soils and transported to leaves [ 85 ]. We observed that these trichome openings also serve as exit points for endophytes to colonize the leaf surface, providing a mechanism that helps to explain the provenance of some phyllosphere microbes, including many seed-derived proteobacteria [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that plants with these endosymbioses may switch to absorb soil nitrogen when that is available. This may be evident in the case of invasive reed grass where plants thrive in nitrogen-contaminated soils [ 85 , 86 , 87 , 88 , 89 ]. More research into stacked symbiosis as a competitiveness and aggressiveness-enhancing trait will need to be conducted to help validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Endophytes utilize the plant's endosphere as a unique niche to protect themselves from drastic changes in the external environment (Schindler et al, 2021). Recently, medicinal plants have been reported to be influenced by their interaction with beneficial endophytes (Lindow and Brandl, 2003;Chaudhry et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Precipitated proteins were pelleted by centrifugation (21,000× g , 15 min, 4 °C) and 950 µL of supernatants was collected, stored at −80 °C for 30 min, and centrifuged again for another 10 min. Five microliters of 10 mM PGP (phenyl-β-D-glucopyranoside) and ten microliters of 2.5 mM raffinose were added as internal standards [ 13 ]. Samples were dried under a gentle nitrogen flow and stored at −80 °C until derivatization.…”
Section: Methodsmentioning
confidence: 99%